Glycated Albumin Triggers an Inflammatory Response in the Human Airway Epithelium and Causes an Increase in Ciliary Beat Frequency - Aitken, Moira L.; Somayaji, Ranjani; Hinds, Thomas R.; Pier, Maricela; Droguett, Karla; Rios, Mariana; Skerrett, Shawn J.; Villalon, Manuel (Frontiers in Physiology, 2021)
The role of inflammation in airway epithelial cells and its regulation are important in several respiratory diseases. When disease is present, the barrier between the pulmonary circulation and airway epithelium is damaged allowing serum proteins to enter the airways. We identified that human glycated albumin (GA) is a molecule in human serum that triggers an inflammatory response in human airway epithelial cultures. We observed that single donor human serum induced IL-8 secretion from primary human airway epithelial cells and from a cystic fibrosis airway cell line (CF1-16) in a dose-dependent manner. IL-8 secretion from airway epithelial cells was time dependent and rapidly increased in the first four hours of incubation. Stimulation with GA promoted epithelial cells to secrete IL-8 and, this increase was blocked by anti-GA antibody. The IL-8 secretion induced by serum GA was 10 to 50-fold more potent than TNFα or LPS stimulation. GA also has a functional effect on airway epithelial cells in vitro increasing ciliary beat frequency. Our results demonstrate that the serum molecule GA is pro-inflammatory and triggers host defense responses including increases in IL-8 secretion and ciliary beat frequency in human airway epithelium. We highlight the importance of GA in airway inflammation which has not been previously well recognized.